Prenatal exposure to polybrominated diphenyl ethers and inattention/hyperactivity symptoms in mid to late adolescents - Park, Seonyoung; Cowell, Whitney; Margolis, Amy E.; Sjodin, Andreas; Jones, Richard; Rauh, Virginia; Wang, Shuang; Herbstman, Julie B. (Frontiers in Epidemiology, 2023)
Prenatal exposure to polybrominated diphenyl ethers (PBDEs) has been associated with increased attention deficit/hyperactivity disorder (ADHD) symptoms in early to middle childhood, as well as early adolescence. However, data are limited for the long-lasting impact of exposure on outcomes assessed across the entire adolescent period, and sex-specificity of such associations. We investigated the association between continuous log10-transformed cord plasma PBDE concentrations and 4th edition ADHD rating scale (ADHD-RS-IV) score from mid adolescence (~11 years old) to late adolescence (~17 years old). The study sample includes a subset (n=219) of the African American and Dominican children enrolled in the Columbia Center for Children’s Environmental Health Mothers and Newborns birth cohort. We used generalized estimating equations (GEE) to account for the repeated measure of ADHD RS scores. We examined interactions between PBDE exposure and sex using cross-product terms and sex-stratified models. Additionally, we used linear regression using age-stratified sample as a sensitivity analysis. Associations between prenatal exposure and parents’ report of ADHD symptoms varied by sex (p-interaction < 0.20), with positive relationships observed among girls but not boys from sex-stratified models. Our finding suggests prenatal PBDE exposure may affect ADHD symptoms assessed during middle to late adolescence and sex-specificity of such impact.